Immobilized microbial nanoparticles for biosorption - Giese, Ellen C.; Silva, Debora D. V. [UNESP]; Costa, Ana F. M.; Almeida, Sâmilla G. C. [UNESP]; Dussán, Kelly J. [UNESP] (Taylor & Francis, 2020)
Biosorption processes emerge as an economical and eco-friendly alternative technology for the removal of pollutants present in the environment. One biosorption process application is found in the immobilization of microbial cells for the removal of toxic pollutants in industrial wastewater. The immobilization of microorganisms on magnetic nano-based carriers is a relevant new technique applied to obtain biocatalysts for environmental pollution control, however, it has been little described in the literature. Magnetic nanoparticles present several advantages when compared to suspended microorganism technology and conventional methods of cell immobilization, such as simple recovery of catalysts from the liquid phase. Considering the relevant application of magnetic nanoparticles as a support for microorganism immobilization, this review aims to present potential studies in the immobilization of bacteria, yeast, and fungi on magnetic nano-based carriers. Immobilization carriers and methods are highlighted and discussed based on their strengths and drawbacks. Isotherm and kinetic models are presented. This review also highlights the application of immobilized microbial nanoparticles in the removal of heavy metals from the environment. The state-of-the art of biosorption technology applying magnetically immobilized cells is presented in this review and provides insights into this research area.
Keywords: biosorption; heavy metals; immobilization; microbial cells; Nanoparticles; toxic pollutants